COX-BAĞINTI MODELİ VE BİR UYGULAMA - ERTEM VEHİT, Hayriye and DİRİCAN, Ahmet and ÖNEŞ, Ülker (Cerrahpaşa Medical Journal, 2014)
Background and Design.- In this study, we have used of the cox-regression model, where by the possible effects of variables on the outcome of some cases who have been longitudinally followed from a certain starting point are analyzed.In an attempt to evaluate variables affecting a result dependent on time, 1000 cases with allergic bronchial asthma have been examined according to the duration of time that they were breast-fed. Taking this duration of time into account, the variables of total IgE and IgA, house dust, epithelium and hair, mould, pollen, wild grass and age groups, which are consider having an affect on the development of bronchial asthma, have been analyzed by means of the cox-correlation model. Results.- It has been observed that a statistically significant difference occurred when house dust and food allergy were positive. Conclusion.- House dust allergy was the only main risk factor for the development of asthma but food allergy was not.